2014
DOI: 10.1051/m2an/2014018
|View full text |Cite
|
Sign up to set email alerts
|

Regularity and approximability of the solutions to the chemical master equation

Abstract: The chemical master equation is a fundamental equation in chemical kinetics. It underlies the classical reaction-rate equations and takes stochastic effects into account. In this paper we give a simple argument showing that the solutions of a large class of chemical master equations are bounded in weighted 1-spaces and possess high-order moments. This class includes all equations in which no reactions between two or more already present molecules and further external reactants occur that add mass to the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…A related existence result for the Markov semigroup of the CME was established in [ 22 ], which however does not apply to the case of reversible RRE, because of the restrictions on the growth of the transition rates.…”
Section: The Chemical Master Equationmentioning
confidence: 99%
“…A related existence result for the Markov semigroup of the CME was established in [ 22 ], which however does not apply to the case of reversible RRE, because of the restrictions on the growth of the transition rates.…”
Section: The Chemical Master Equationmentioning
confidence: 99%
“…In this approach all the outgoing transitions from the truncated state-space are simply eliminated by setting their propensities to zero. It has been shown that this reflected version of FSP yields accurate estimates of the stationary distribution for some reaction network examples [17,12]. However there is no theoretical guarantee that this approach will work well in general.…”
Section: Introductionmentioning
confidence: 99%
“…For all models encountered in practice, the error bound g(t) decreases monotonically as Ω expands [42]. Under some regularity conditions on the propensity functions, it could be shown that p(t) −p Ω (t) 1 → 0 as Ω → S [22]. 3.1.…”
Section: Where (26)mentioning
confidence: 97%